Preparation method of small-particle doped cobaltosic oxide material

By using sulfoxide chloride to modify polyethylene glycol monomethyl ether and water-soluble polymerized ionic liquid in the preparation of doped tricobalt oxide materials, the problem of easy agglomeration of small-particle doped tricobalt oxide materials is solved, and smaller particle sizes and higher Properties of material preparation.

CN119490235AActive Publication Date: 2025-02-21YANGJIANG FEDERAL METAL CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411714087.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-21
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing doped cobalt oxide materials are prone to agglomeration at small particle sizes, which limits their performance improvement in photocatalysis, batteries and other fields.

Method used

Polyethylene glycol monomethyl ether is modified with sulfoxide chloride to prepare an ionic liquid containing double bonds, and a water-soluble polymerized ionic liquid is obtained by polymerizing double bonds with acrylamide. The liquid is compounded with cetyltrimethylammonium bromide, and undergoes a hydrothermal reaction in deionized water. Urea and cobalt nitrate hexahydrate are used as precipitant and cobalt source to prepare small particles doped with cobalt material.

Benefits of technology

The doped cobalt tetroxide material prepared by this method not only has a small particle size, but also reduces agglomeration and improves the performance and application potential of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005156488860000101
    Figure BDA0005156488860000101
  • Figure BDA0005156488860000111
    Figure BDA0005156488860000111
Patent Text Reader

Abstract

The invention relates to a preparation method of a small-particle doped cobaltosic oxide material, and belongs to the technical field of cobaltosic oxide. The preparation method comprises the following steps: performing halogen modification on polyethylene glycol monomethyl ether by using thionyl chloride to obtain polyethylene glycol monomethyl ether of which the terminal hydroxyl is substituted by chlorine atoms, then adding N-vinyl imidazole, preparing ionic liquid containing double bonds under the action of the chlorine atoms and-N =, and then adding acrylamide to perform double-bond polymerization, thereby obtaining the ionic liquid containing the double bonds. The water-soluble polymerized ionic liquid with an amino repeating unit at one end and an ether bond repeating unit at the other end is compounded with hexadecyl trimethyl ammonium bromide; when deionized water is used as a solvent, urea is used as a precipitator, cobalt nitrate hexahydrate is used as a cobalt source and a doping agent is contained, a hydrothermal reaction is carried out, an excellent dispersion effect can be exerted on a precursor, interaction force among particles is also greatly reduced during aging, and finally, the prepared cobaltosic oxide-doped material is small in particle size and good in dispersity. And agglomeration is also reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of cobalt tetroxide, and in particular relates to a method for preparing a small particle doped cobalt tetroxide material. Background Art

[0002] Cobalt tetroxide is an inorganic particle in the form of a black or gray-black powder with a chemical formula of Co3O4. It is widely used in photocatalysis, batteries, energy, gas sensing and other fields due to its many excellent characteristics such as low bandgap energy, high energy storage efficiency and good stability. A large number of studies have shown that compared with pure cobalt tetroxide, cobalt tetroxide materials doped with other metal elements can often exhibit better performance. For example, doping with chromium elements can enhance catalytic performance, and doping with tin elements can increase capacitance. Among them, the preparation method of doped cobalt tetroxide materials usually adopts liquid phase precipitation method. The particle size of the doped particles is small and can reach the nanometer scale. However, this leads to the fact that the doped cobalt tetroxide materials prepared by the liquid phase precipitation method still have certain disadvantages that limit their actual technical effects. This is because the smaller the size of the doped particles, the more obvious the agglomeration problem will be, which will seriously restrict the subsequent performance improvement when used in various fields. Summary of the invention

[0003] In view of the problems existing in the prior art, the purpose of the present invention is to provide a preparation method of a small particle doped cobalt oxide material. The present invention firstly uses thionyl chloride to perform halogen modification on polyethylene glycol monomethyl ether to obtain polyethylene glycol monomethyl ether in which the terminal hydroxyl group is replaced by a chlorine atom, then adds N-vinyl imidazole, and prepares an ionic liquid containing a double bond through the action of the chlorine atom and -N=, and then adds acrylamide to polymerize the double bonds to obtain a water-soluble polymerized ionic liquid with an amino repeating unit at one end and an ether bond repeating unit at the other end, and compounding hexadecyltrimethylammonium bromide with the ionic liquid. When a hydrothermal reaction occurs in the presence of deionized water as a solvent, urea as a precipitant, hexahydrated cobalt nitrate as a cobalt source, and a dopant, the precursor can be excellently dispersed, and the interaction force between particles is greatly reduced during aging, so that the prepared doped cobalt oxide material not only has a small particle size, but also reduces agglomeration.

[0004] The purpose of the present invention can be achieved through the following technical solutions:

[0005] A method for preparing a small particle doped cobalt oxide material, the method comprising the following steps:

[0006] (1) adding cobalt nitrate hexahydrate, urea, hexadecyltrimethylammonium bromide and a water-soluble polymeric ionic liquid to deionized water, and then stirring and mixing at room temperature for 5-10 minutes to obtain material A;

[0007] (2) adding a dopant to the material A and subjecting it to a hydrothermal reaction to obtain material B;

[0008] (3) cooling the material B to room temperature at room temperature and pressure, aging for 1-1.5 hours, filtering, removing the filtrate, washing with deionized water, and drying to obtain material C;

[0009] (4) The material C is heated and then calcined to complete the preparation.

[0010] As a preferred technical solution of the present invention, in step (1), the mass ratio of the deionized water, the cobalt nitrate hexahydrate, the urea, the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid is 80:2-3:5:0.5:1-1.5.

[0011] As a preferred technical solution of the present invention, the water-soluble polymeric ionic liquid in step (1) is prepared by the following steps:

[0012] Step A: adding 8-10 parts by weight of polyethylene glycol monomethyl ether and 2-2.5 parts by weight of pyridine to 80-100 parts by weight of toluene, and then dropping 4-5 parts by weight of thionyl chloride under stirring in an argon atmosphere under an ice bath, heating to 100-110° C. after the dropwise addition is completed, then stirring at this temperature for 48 hours, cooling naturally to room temperature, removing impurities, and obtaining component A;

[0013] Step B: 4-5 parts by weight of component A and 1 part by weight of N-vinyl imidazole are stirred at 90-100° C. for 24-26 hours in an argon atmosphere, then washed alternately with ethyl acetate and diethyl ether 2-3 times, and finally vacuum dried at 50-70° C. until constant weight is obtained to obtain component B;

[0014] Step C: add 15-20 parts by weight of deionized water to 40 parts by weight of tetrahydrofuran, stir and mix at room temperature for 5-10 minutes, then add 4-5 parts by weight of component B, 1-1.5 parts by weight of acrylamide and 0.1-0.2 parts by weight of potassium persulfate, stir at 60-65° C. for 4-6 hours, distill under reduced pressure, filter and remove insoluble matter, and the preparation is completed.

[0015] Furthermore, the polyethylene glycol monomethyl ether in step A is at least one of polyethylene glycol monomethyl ether 350 and polyethylene glycol monomethyl ether 600.

[0016] Furthermore, the dripping rate in step A is controlled at 1-3 drops / s.

[0017] Furthermore, the heating rate in step A is controlled at 3-5°C / min.

[0018] Furthermore, the impurity removal in step A refers to collecting the upper layer of liquid, then adding 2.5% by volume of a saturated sodium bicarbonate aqueous solution at room temperature, stirring for 5-10 minutes to mix, then adding 40-50 parts by weight of dichloromethane, shaking 5-7 times, standing for 5-10 minutes, taking the lower layer of liquid, distilling at 40°C until the volatiles are completely removed, washing with deionized water, and finally vacuum drying at 50-70°C until constant weight.

[0019] Furthermore, the reduced pressure distillation in step C refers to distillation at 50° C. under a vacuum degree of -0.06 MPa until the volatiles are completely removed.

[0020] As a preferred technical solution of the present invention, the mass ratio of the cobalt nitrate hexahydrate in step (1) to the dopant in step (2) is 1:0.005-0.01; the dopant in step (2) is one of potassium nitrate, iron nitrate, magnesium nitrate, lithium nitrate and nickel nitrate.

[0021] As a preferred technical solution of the present invention, the reaction conditions of the hydrothermal reaction in step (2) are pressure 25-28 kPa, temperature 100-105° C., and time 10-12 h.

[0022] As a preferred technical solution of the present invention, the drying in step (3) refers to vacuum drying at 105° C. until constant weight.

[0023] As a preferred technical solution of the present invention, the heating and calcination in step (4) refers to heating to 350-400°C at a heating rate of 8-10°C / min in an oxygen atmosphere and then calcining for 3-3.5h.

[0024] Beneficial effects of the present invention:

[0025] (1) The present invention first uses thionyl chloride to halogen-modify polyethylene glycol monomethyl ether to obtain polyethylene glycol monomethyl ether in which the terminal hydroxyl group is replaced by a chlorine atom, then adds N-vinyl imidazole, and prepares an ionic liquid containing a double bond through the action of the chlorine atom and -N=, and then adds acrylamide to polymerize the double bonds to obtain a water-soluble polymerized ionic liquid with an amino repeating unit at one end and an ether bond repeating unit at the other end, and then compounding hexadecyltrimethylammonium bromide with it. When a hydrothermal reaction is carried out in the presence of deionized water as a solvent, urea as a precipitant, hexahydrated cobalt nitrate as a cobalt source, and a dopant, the precursor can be excellently dispersed, and the interaction force between particles is greatly reduced during aging, so that the prepared doped cobalt oxide material not only has a small particle size, but also reduces agglomeration.

[0026] (2) The present invention, without changing the prior art that the liquid phase precipitation method for the preparation of precursors mostly uses deionized water as the solvent, creatively prepares a water-soluble polymeric ionic liquid, which can produce an excellent synergistic effect when compounded with hexadecyltrimethylammonium bromide and dissolved in deionized water, and jointly play a role in dispersing the precursor; the addition of the water-soluble polymeric ionic liquid can, on the one hand, reduce the surface tension of the entire system, thereby achieving the dispersion of the precursor; on the other hand, due to the presence of a certain degree of polymerization structure, it has a stronger hydrogen bonding effect and a large number of hydrogen bonding networks, which can "cover" the surface of the precursor in the system and hinder the occurrence of agglomeration, especially in the aging process, which can greatly reduce the interaction force between the particles during growth, thereby reducing the agglomeration; at the same time, compared with the prior art that directly replaces deionized water as a solvent with an ionic liquid, the water-soluble polymeric ionic liquid of the present invention has stronger universality and is added to the system in the form of an auxiliary agent, without considering the solubility of other substances such as cobalt sources and dopants in it. DETAILED DESCRIPTION

[0027] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0028] Example 1

[0029] A method for preparing a small particle doped cobalt oxide material, the method comprising the following steps:

[0030] (1) adding cobalt nitrate hexahydrate, urea, hexadecyltrimethylammonium bromide and a water-soluble polymeric ionic liquid into deionized water, and then stirring and mixing at room temperature for 5 minutes to obtain a material A;

[0031] (2) adding a dopant to the material A and subjecting it to a hydrothermal reaction to obtain material B;

[0032] (3) cooling the material B to room temperature at room temperature and pressure, aging it for 1 hour, filtering it, removing the filtrate, washing it with deionized water, and drying it to obtain material C;

[0033] (4) The material C is heated and then calcined to complete the preparation.

[0034] In step (1), the mass ratio of the deionized water, the cobalt nitrate hexahydrate, the urea, the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid is 80:2:5:0.5:1.

[0035] The water-soluble polymeric ionic liquid of step (1) is prepared by the following steps:

[0036] Step A: Add 8 parts by weight of polyethylene glycol monomethyl ether and 2 parts by weight of pyridine to 80 parts by weight of toluene, then dropwise add 4 parts by weight of thionyl chloride under stirring in an ice bath in an argon atmosphere, heat to 100° C. after the addition is complete, then keep warm and stir for 48 hours, cool naturally to room temperature, remove impurities, and obtain component A;

[0037] Step B: 4 parts by weight of component A and 1 part by weight of N-vinyl imidazole were stirred at 90° C. for 24 hours in an argon atmosphere, then washed twice with ethyl acetate and diethyl ether alternately, and finally dried under vacuum at 50° C. until constant weight was obtained to obtain component B;

[0038] Step C: Add 15 parts by weight of deionized water to 40 parts by weight of tetrahydrofuran, and then stir at room temperature for 5 minutes to mix, then add 4 parts by weight of component B, 1 part by weight of acrylamide and 0.1 parts by weight of potassium persulfate, and finally stir at 60°C for 4 hours, distill under reduced pressure, filter, remove insoluble matter, and the preparation is completed.

[0039] The polyethylene glycol monomethyl ether in step A is polyethylene glycol monomethyl ether 350.

[0040] The dripping rate in step A is controlled at 1 drop / s.

[0041] The heating rate in step A is controlled at 3°C / min.

[0042] The impurity removal in step A refers to collecting the upper layer of liquid, then adding 2.5% by volume of a saturated sodium bicarbonate aqueous solution at room temperature, stirring for 5 minutes, then adding 40 parts by weight of dichloromethane, shaking 5 times, standing for 5 minutes, taking the lower layer of liquid, distilling at 40°C until the volatiles are completely removed, washing with deionized water, and finally vacuum drying at 50°C until constant weight.

[0043] The reduced pressure distillation in step C refers to distillation at 50° C. under a vacuum degree of -0.06 MPa until the volatiles are completely removed.

[0044] The mass ratio of the cobalt nitrate hexahydrate in step (1) to the dopant in step (2) is 1:0.005; the dopant in step (2) is potassium nitrate.

[0045] The reaction conditions of the hydrothermal reaction in step (2) are pressure 25 kPa, temperature 100° C., and time 10 h.

[0046] The drying in step (3) refers to vacuum drying at 105° C. until constant weight.

[0047] The heating and calcination in step (4) refers to heating to 350° C. at a heating rate of 8° C. / min in an oxygen atmosphere and then calcining for 3 hours.

[0048] Example 2

[0049] A method for preparing a small particle doped cobalt oxide material, the method comprising the following steps:

[0050] (1) adding cobalt nitrate hexahydrate, urea, hexadecyltrimethylammonium bromide and a water-soluble polymeric ionic liquid to deionized water, and then stirring and mixing at room temperature for 10 minutes to obtain a material A;

[0051] (2) adding a dopant to the material A and subjecting it to a hydrothermal reaction to obtain material B;

[0052] (3) cooling the material B to room temperature at room temperature and pressure, aging it for 1.5 hours, filtering it, removing the filtrate, washing it with deionized water, and drying it to obtain material C;

[0053] (4) The material C is heated and then calcined to complete the preparation.

[0054] In step (1), the mass ratio of the deionized water, the cobalt nitrate hexahydrate, the urea, the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid is 80:3:5:0.5:1.5.

[0055] The water-soluble polymeric ionic liquid of step (1) is prepared by the following steps:

[0056] Step A: add 10 parts by weight of polyethylene glycol monomethyl ether and 2.5 parts by weight of pyridine to 100 parts by weight of toluene, then add dropwise 5 parts by weight of thionyl chloride under stirring in an ice bath in an argon atmosphere, heat to 110° C. after the addition is complete, then keep warm and stir for 48 hours, cool naturally to room temperature, remove impurities, and obtain component A;

[0057] Step B: 5 parts by weight of component A and 1 part by weight of N-vinyl imidazole are stirred at 100° C. for 26 hours in an argon atmosphere, then washed alternately with ethyl acetate and diethyl ether three times, and finally dried in vacuo at 70° C. until constant weight is obtained to obtain component B;

[0058] Step C: Add 20 parts by weight of deionized water to 40 parts by weight of tetrahydrofuran, and then stir and mix at room temperature for 10 minutes, then add 5 parts by weight of component B, 1.5 parts by weight of acrylamide and 0.2 parts by weight of potassium persulfate, and finally stir at 65°C for 6 hours, distill under reduced pressure, filter, and remove insoluble matter, and the preparation is completed.

[0059] The polyethylene glycol monomethyl ether in step A is polyethylene glycol monomethyl ether 350.

[0060] The rate of the dripping in step A is controlled at 3 drops / s.

[0061] The heating rate in step A is controlled at 5°C / min.

[0062] The impurity removal in step A refers to collecting the upper layer of liquid, then adding 2.5% by volume of a saturated sodium bicarbonate aqueous solution at room temperature, stirring for 10 minutes, then adding 50 parts by weight of dichloromethane, shaking 7 times, standing for 10 minutes, taking the lower layer of liquid, distilling at 40°C until the volatiles are completely removed, washing with deionized water, and finally vacuum drying at 70°C until constant weight.

[0063] The reduced pressure distillation in step C refers to distillation at 50° C. under a vacuum degree of -0.06 MPa until the volatiles are completely removed.

[0064] The mass ratio of the cobalt nitrate hexahydrate in step (1) to the dopant in step (2) is 1:0.01; the dopant in step (2) is potassium nitrate.

[0065] The reaction conditions of the hydrothermal reaction in step (2) are pressure 28 kPa, temperature 105° C., and time 12 h.

[0066] The drying in step (3) refers to vacuum drying at 105° C. until constant weight.

[0067] The heating and calcination in step (4) refers to heating to 400°C at a heating rate of 10°C / min in an oxygen atmosphere and then calcining for 3.5 hours.

[0068] Example 3

[0069] A method for preparing a small particle doped cobalt oxide material, the method comprising the following steps:

[0070] (1) adding cobalt nitrate hexahydrate, urea, hexadecyltrimethylammonium bromide and a water-soluble polymeric ionic liquid into deionized water, and then stirring and mixing at room temperature for 8 minutes to obtain a material A;

[0071] (2) adding a dopant to the material A and subjecting it to a hydrothermal reaction to obtain material B;

[0072] (3) cooling the material B to room temperature at room temperature and pressure, aging it for 1.3 h, filtering it, removing the filtrate, washing it with deionized water, and drying it to obtain material C;

[0073] (4) The material C is heated and then calcined to complete the preparation.

[0074] The mass ratio of the deionized water, the cobalt nitrate hexahydrate, the urea, the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid in step (1) is 80:2.5:5:0.5:1.3.

[0075] The water-soluble polymeric ionic liquid of step (1) is prepared by the following steps:

[0076] Step A: Add 9 parts by weight of polyethylene glycol monomethyl ether and 2.3 parts by weight of pyridine to 90 parts by weight of toluene, then dropwise add 4.5 parts by weight of thionyl chloride under an argon atmosphere in an ice bath while stirring, and after the dropwise addition is completed, heat to 105° C., then keep warm and stir for 48 hours, naturally cool to room temperature, remove impurities, and obtain component A;

[0077] Step B: 4.5 parts by weight of component A and 1 part by weight of N-vinyl imidazole were stirred at 95° C. for 25 h in an argon atmosphere, then washed alternately with ethyl acetate and diethyl ether for 3 times, and finally dried in vacuo at 60° C. until constant weight was obtained to obtain component B;

[0078] Step C: Add 18 parts by weight of deionized water to 40 parts by weight of tetrahydrofuran, and then stir at room temperature for 8 minutes to mix, then add 4.5 parts by weight of component B, 1.3 parts by weight of acrylamide and 0.15 parts by weight of potassium persulfate, and finally stir at 63° C. for 5 hours, distill under reduced pressure, filter, and remove insoluble matter, and the preparation is completed.

[0079] The polyethylene glycol monomethyl ether in step A is polyethylene glycol monomethyl ether 350.

[0080] The dripping rate in step A is controlled at 2 drops / s.

[0081] The heating rate in step A is controlled at 4°C / min.

[0082] The impurity removal in step A refers to collecting the upper layer of liquid, then adding 2.5% by volume of a saturated sodium bicarbonate aqueous solution at room temperature, stirring for 8 minutes, then adding 45 parts by weight of dichloromethane, shaking 6 times, standing for 8 minutes, taking the lower layer of liquid, distilling at 40°C until the volatiles are completely removed, washing with deionized water, and finally vacuum drying at 60°C until constant weight.

[0083] The reduced pressure distillation in step C refers to distillation at 50° C. under a vacuum degree of -0.06 MPa until the volatiles are completely removed.

[0084] The mass ratio of the cobalt nitrate hexahydrate in step (1) to the dopant in step (2) is 1:0.008; the dopant in step (2) is potassium nitrate.

[0085] The reaction conditions of the hydrothermal reaction in step (2) are pressure 26 kPa, temperature 103° C., and time 11 h.

[0086] The drying in step (3) refers to vacuum drying at 105° C. until constant weight.

[0087] The heating and calcination in step (4) refers to heating to 380°C at a heating rate of 9°C / min in an oxygen atmosphere and then calcining for 3.2h.

[0088] Comparative Example 1

[0089] On the basis of Example 1, hexadecyltrimethylammonium bromide was replaced by an equal weight of water-soluble polymeric ionic liquid, and the rest remained unchanged.

[0090] Comparative Example 2

[0091] On the basis of Example 1, the water-soluble polymeric ionic liquid was replaced with an equal weight of hexadecyltrimethylammonium bromide, and the rest remained unchanged.

[0092] Comparative Example 3

[0093] On the basis of Example 1, hexadecyltrimethylammonium bromide and water-soluble polymeric ionic liquid are not added in step (1), but are added after the hydrothermal reaction in step (2), and the rest remain unchanged.

[0094] Comparative Example 4

[0095] On the basis of Example 1, hexadecyltrimethylammonium bromide was replaced by an equal weight of water-soluble polymeric ionic liquid. Meanwhile, the water-soluble polymeric ionic liquid was not added in step (1) but was added after the hydrothermal reaction in step (2). The rest remained unchanged.

[0096] Comparative Example 5

[0097] On the basis of Example 1, the water-soluble polymeric ionic liquid is replaced by an equal weight of hexadecyltrimethylammonium bromide. Meanwhile, hexadecyltrimethylammonium bromide is not added in step (1) but is added after the hydrothermal reaction in step (2). The rest remain unchanged.

[0098] Comparative Example 6

[0099] On the basis of Example 1, 1 part by weight of acrylamide in step C was changed to 0.6 parts by weight of acrylamide, and the rest remained unchanged.

[0100] Comparative Example 7

[0101] On the basis of Example 1, hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid were replaced with equal weights of deionized water, and the rest remained unchanged.

[0102] Test Example 1

[0103] Performance Test:

[0104] The small particle doped cobalt tetroxide materials prepared in Examples 1-3 and Comparative Examples 1-7 were respectively subjected to sensitivity tests using a CGS-MT intelligent gas sensing test system, where sensitivity = R1 / R0, where R1 is the resistance value of the sensor in the response gas, and R0 is the resistance value of the sensor in the air.

[0105] Table 1. Performance test results

[0106]

[0107]

[0108] Comparison between Example 1 and Comparative Examples 1-7 shows that:

[0109] The difference between Comparative Example 1 and Example 1 is that hexadecyltrimethylammonium bromide is replaced by an equal weight of water-soluble polymeric ionic liquid.

[0110] The difference between Comparative Example 2 and Example 1 is that the water-soluble polymeric ionic liquid is replaced by an equal weight of hexadecyltrimethylammonium bromide.

[0111] The difference between Comparative Example 3 and Example 1 is that hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid are added after the hydrothermal reaction is completed.

[0112] The difference between Comparative Example 4 and Example 1 is that hexadecyltrimethylammonium bromide is replaced by an equal weight of water-soluble polymeric ionic liquid, and the water-soluble polymeric ionic liquid is added after the hydrothermal reaction is completed.

[0113] The difference between Comparative Example 5 and Example 1 is that the water-soluble polymeric ionic liquid is replaced by an equal weight of hexadecyltrimethylammonium bromide, and the hexadecyltrimethylammonium bromide is added after the hydrothermal reaction is completed.

[0114] The difference between Comparative Example 6 and Example 1 is that the number of amino repeating units in the water-soluble polymeric ionic liquid is reduced.

[0115] The difference between Comparative Example 7 and Example 1 is that the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid are replaced by equal weights of deionized water.

[0116] From the comparison between Example 1 and Comparative Examples 1-7 in Test Example 1, it can be seen that the small-particle doped cobalt oxide material prepared by the present invention has more excellent performance, which indirectly shows that its agglomeration is relatively less, and correspondingly the technical effect achieved is better.

[0117] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a small particle doped cobalt oxide material, characterized in that: The preparation method comprises the following steps: (1) adding cobalt nitrate hexahydrate, urea, hexadecyltrimethylammonium bromide and a water-soluble polymeric ionic liquid to deionized water, and then stirring and mixing at room temperature for 5-10 minutes to obtain material A; (2) adding a dopant to the material A and subjecting it to a hydrothermal reaction to obtain material B; (3) cooling the material B to room temperature at room temperature and pressure, aging for 1-1.5 hours, filtering, removing the filtrate, washing with deionized water, and drying to obtain material C; (4) The material C is heated and then calcined to complete the preparation.

2. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: In step (1), the mass ratio of the deionized water, the cobalt nitrate hexahydrate, the urea, the hexadecyltrimethylammonium bromide and the water-soluble polymeric ionic liquid is 80:2-3:5:0.5:1-1.

5.

3. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: The water-soluble polymeric ionic liquid of step (1) is prepared by the following steps: Step A: adding 8-10 parts by weight of polyethylene glycol monomethyl ether and 2-2.5 parts by weight of pyridine to 80-100 parts by weight of toluene, and then dropping 4-5 parts by weight of thionyl chloride under stirring in an argon atmosphere under an ice bath, heating to 100-110° C. after the dropwise addition is completed, then stirring at this temperature for 48 hours, cooling naturally to room temperature, removing impurities, and obtaining component A; Step B: 4-5 parts by weight of component A and 1 part by weight of N-vinyl imidazole are stirred at 90-100° C. for 24-26 hours in an argon atmosphere, then washed alternately with ethyl acetate and diethyl ether 2-3 times, and finally vacuum dried at 50-70° C. until constant weight is obtained to obtain component B; Step C: add 15-20 parts by weight of deionized water to 40 parts by weight of tetrahydrofuran, stir and mix at room temperature for 5-10 minutes, then add 4-5 parts by weight of component B, 1-1.5 parts by weight of acrylamide and 0.1-0.2 parts by weight of potassium persulfate, stir at 60-65° C. for 4-6 hours, distill under reduced pressure, filter and remove insoluble matter, and the preparation is completed.

4. The method for preparing a small particle doped cobalt oxide material according to claim 3, characterized in that: The polyethylene glycol monomethyl ether in step A is at least one of polyethylene glycol monomethyl ether 350 and polyethylene glycol monomethyl ether 600.

5. The method for preparing a small particle doped cobalt oxide material according to claim 3, characterized in that: The impurity removal in step A refers to collecting the upper layer of liquid, then adding 2.5% by volume of a saturated sodium bicarbonate aqueous solution at room temperature, stirring for 5-10 minutes, then adding 40-50 parts by weight of dichloromethane, shaking 5-7 times, standing for 5-10 minutes, taking the lower layer of liquid, distilling at 40° C. until the volatiles are completely removed, washing with deionized water, and finally vacuum drying at 50-70° C. until constant weight.

6. The method for preparing a small particle doped cobalt oxide material according to claim 3, characterized in that: The reduced pressure distillation in step C refers to distillation at 50° C. under a vacuum degree of -0.06 MPa until the volatiles are completely removed.

7. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: The mass ratio of the cobalt nitrate hexahydrate in step (1) to the dopant in step (2) is 1:0.005-0.01; the dopant in step (2) is one of potassium nitrate, iron nitrate, magnesium nitrate, lithium nitrate and nickel nitrate.

8. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: The reaction conditions of the hydrothermal reaction in step (2) are pressure 25-28 kPa, temperature 100-105° C., and time 10-12 h.

9. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: The drying in step (3) refers to vacuum drying at 105° C. until constant weight.

10. The method for preparing a small particle doped cobalt oxide material according to claim 1, characterized in that: The heating and calcination in step (4) refers to heating to 350-400°C at a heating rate of 8-10°C / min in an oxygen atmosphere and then calcining for 3-3.5h.

Citation Information

Patent Citations

  • Method for preparing cobaltosic oxide material through eutectic ionic liquid

    CN114105219A

  • Cobaltosic oxide nano composite catalyst

    CN116247228A

  • Polymer-modified nanoparticle

    JP2006056999A

  • Infrared-ray-absorbable thin film containing rutile-type titanium oxide crystals, and process for production thereof

    WO2011135974A1